Transformasi UMKM Kajoetangan Heritage: Peran Pelatihan Kewirausahaan Kreativitas dan Motivasi dalam Meningkatkan Pengembangan Usaha - Fatmasari Endayani; Sudarmiatin, Sudarmiatin; Ludi Wishnu Wardana (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
This study aims to analyze the role of entrepreneurship training, creativity, and motivation in enhancing the business development of MSMEs in Kajoetangan Heritage. MSMEs in this area have significant potential to support the local economy but face challenges in adapting to a rapidly changing business environment. Business transformation through entrepreneurship training is expected to facilitate the improvement of skills and knowledge among MSME actors, while creativity plays a role in generating competitive product and service innovations. Furthermore, high motivation is identified as a crucial factor influencing business enthusiasm in facing market competition. Through a quantitative approach using a survey method, this study involves 120 business owners of MSMEs in Kajoetangan Heritage, with all of them included as the sample. The results indicate that both entrepreneurship training and creativity have a significant and positive impact on business development. However, motivation has an insignificant effect on business development. These findings are expected to provide insights for the government and other stakeholders in designing sustainable MSME development strategies.